A practical guide to peritoneal malignancy : the PMI manual - Cecil, Tom (Colorectal surgeon); Bunni, John; Mehta, Akash (Boca Raton, FL : CRC Press, 2019)
"Peritoneal malignancy is a rapidly growing field within surgical oncology. A large body of evidence now exists, but the practical implications of this evidence base remain unclear. The Peritoneal Malignancy Institute in Basingstoke, the largest centre in the world, is at the forefront of new developments and techniques. This manual combines the experience of the PMI with the latest evidence to provide a practice-oriented guide to the successful set up and running of a peritoneal malignancy unit"--
Appendix tumours and pseudomyxoma peritonei a "paradigm" for peritoneal disease / Akash Mehta and Tom Cecil -- Colorectal Peritoneal metastases / John Bunni and Brendan Moran -- Peritoneal mesothelioma / Faraz Khan and Faheez Mohamed -- Miscellaneous peritoneal malignancies / Andreas Brandl and Akash Mehta -- Quantitative Assessment of Peritoneal Disease / John Bunni and Sanjeev Dayal -- Imaging in Peritoneal Malignancy / Anuradha Chandramohan & Andrew Thrower -- Intraperitoneal Chemotherapy / Akash Mehta and Faheez Mohamed -- Peri-Operative and Anaesthetic Care / Nina Kashani and John Bell -- Cytoreductive surgery and HIPEC / John Bunni and Tom Cecil -- Postoperative care / Nina Kashani and James Coakes -- Postoperative complication / Kim Govaerts and Brendan Moran -- Histopathological Aspects of Peritoneal Malignancy / Babatunde Rowaiye and Norman Carr -- Follow-Up Protocols in Peritoneal Malignancy / Anuradha Chandramohan, Sourav Panda and Nehal Shah -- Treatment options for recurrence / Jamish Ghandi and Alexios Tzivanakis -- Future perspectives in peritoneal malignancy / Ioanna Panagiotopoulou and Tom Cecil.
OCLC-licensed vendor bibliographic record.
Keywords: Peritoneum -- Cancer -- Treatment; MEDICAL / Surgery / General; MEDICAL / Oncology